Biological Intrusion Prevention and Self-Healing Model for Network Security - Muna, Elsadig; Azween, Abdullah (2010)
This paper describes a new approach for network security based on the combination of biological intrusion prevention and self-healing concepts. The presented system integrates an artificial immune intrusion prevention system for network security inspired by immunological theory known as danger theory. The approach is based upon data inspired by the human immune system (HIS). The IPS analyzes the malicious activities and their effect to trigger the self-healing system. That is detection of the damage caused by malicious activities is used to start the self - healing (SH) mechanism. This system is automated and enhances the fault repair and system recovery.